OVERVIEW OF EARLY CHILDHOOD CARIES AND PREVENTION PRACTICES IN PRESCHOOL CHILDREN IN PONTIANAK - Rhabiah El Fithriyah; Rina Putri Noer Fadilah; Muhammad Fiqri Pratama (Fakultas Kedokteran Gigi Unjani, 2023)
Early Childhood Caries (ECC) is a dental caries disease in children characterized by one or more carious lesions (cavitary or non-cavitated), primary teeth missing/removed due to caries, or primary teeth filled in children under 71 months of age. Prevention of ECC can be done from the time of pregnancy, which aims to prevent the transmission of bacteria that cause dental caries from mother to child. Prevention of ECC continues when the baby is born with the help of parents to keep the child's teeth clean and maintain the child's diet. The research aims to discover how ECC describes and practices prevention in preschool children in Pontianak City. This research design is descriptive to see an overview of ECC and its prevention practices in preschoolers. Results DMFT examination on 107 kindergarten children aged 3-5 years, 13 children were free from caries, while 94 children had caries. Caries' status in the calculation of the DMFT index was determined according to WHO criteria, namely 0.0-1.1 very low, 1.2-2.6 low, 2.7-4.4 moderate, 4.5-6.5 high, >6,6 is very high. The DMFT index status assessment results get an average DMFT index value of 7,046, which is included in the very high category. Meanwhile, the average ECC prevention practice for children in Pontianak is 63.72%, which is included in the good category. Based on the research results, it can be concluded that the caries status of kindergarten children aged 3-5 years in Pontianak City obtained the DMFT index, which includes the very high category. While preventing ECC in kindergarten children aged 3-5 years in the city of Pontianak obtained scores included in the good category. Expected with this research, parents can better maintain and improve their health and well-being by applying knowledge about how to maintain children's dental and oral health so that they can give directions to children better to maintain good oral and dental health and the age of 3-5 years are very susceptible to caries. DOI : 10.54052/jhds.v3n2.p115-124